The Role of Commercial Law in Handling Business Disputes in Indonesia: A Literature Review - Laila Rizqillah; Vivian Alyssa Chandra; Ryan fahri rangkuti; Aulia putri; Ahmad Syaugi Rifai Rabbani (ISNU Sumatera Utara, 2025)
This study examines the role of commercial law in resolving business disputes in Indonesia, focusing on the legal framework, dispute resolution institutions, and implementation challenges. This literature review explores how commercial law, including the Commercial Code (KUHD), Law Number 30 of 1999 concerning Arbitration, and the Electronic Information and Transactions Law (UU ITE), contributes to creating justice, legal certainty, and efficiency in resolving business conflicts. Furthermore, this study analyzes the importance of harmonizing domestic law with international standards to support global trade. The findings indicate that although mechanisms such as arbitration and mediation have become effective alternatives, challenges such as high costs, low legal literacy, and gaps in the implementation of earbitration still hamper the effectiveness of dispute resolution. This article provides strategic recommendations, including increasing the accessibility of arbitration institutions and commercial courts, developing e-arbitration, and improving legal literacy for business actors. This study is expected to serve as a reference in strengthening the role of commercial law in supporting a fair and sustainable business climate in Indonesia.